Existence of periodic solutions for totally nonlinear neutral differential equations with functional delay - Ernest Yankson (Opuscula Mathematica, 2012)
We use a variant of Krasnoselskii's fixed point theorem by T. A. Burton to show that the nonlinear neutral differential equation with functional delay \[x'(t) = -a(t)h(x(t)) +c(t)x'(t-g(t)) + q(t,x(t) x(t-g(t)))\] has a periodic solution.